Quantifying Efficiency Limitations in All‐Inorganic Halide Perovskite Solar Cells. Issue 21 (28th March 2022) - Yuan, Ye; Yan, Genghua; Hong, Ruijiang; Liang, Zongcun; Kirchartz, Thomas
Abstract: While halide perovskites have excellent optoelectronic properties, their poor stability is a major obstacle toward commercialization. There is a strong interest to move away from organic A‐site cations such as methylammonium and formamidinium toward Cs with the aim of improving thermal stability of the perovskite layers. While the optoelectronic properties and the device performance of Cs‐based all‐inorganic lead‐halide perovskites are very good, they are still trailing behind those of perovskites that use organic cations. Here, the state‐of‐the‐art of all‐inorganic perovskites for photovoltaic applications is reviewed by performing detailed meta‐analyses of key performance parameters on the cell and material level. Key material properties such as carrier mobilities, external photoluminescence quantum efficiency, and photoluminescence lifetime are discussed and what is known about defect tolerance in all‐inorganic is compared relative to hybrid (organic–inorganic) perovskites. Subsequently, a unified approach is adopted for analyzing performance losses in perovskite solar cells based on breaking down the losses into several figures of merit representing recombination losses, resistive losses, and optical losses. Based on this detailed loss analysis, guidelines are eventually developed for future performance improvement of all‐inorganic perovskite solar cells. Abstract : The state‐of‐the‐art of all‐inorganic perovskite solar cells is reviewed by performing a detailed meta‐analysis of key performance parameters. Using a consistent way of determining the bandgap, a unified approach is adopted for analyzing performance losses in perovskite solar cells based on breaking down the losses into several figures of merit representing recombination losses, resistive losses, and optical losses.